A HISTORY OF CONCUSSIONS IS ASSOCIATED WITH SYMPTOMS OF COMMON MENTAL DISORDERS IN FORMER MALE PROFESSIONAL ATHLETES ACROSS A RANGE OF SPORTS. Issue 4 (1st February 2017) - Gouttebarge, Vincent; Aoki, Haruhito; Lambert, Mike; Stewart, William; Kerkhoffs, Gino
Abstract : Background: Recent reports suggest that exposure to repetitive concussions in sports is associated with an increased risk of symptoms of Common Mental Disorders (CMD) and of later development of neurodegenerative diseases, in particular chronic traumatic encephalopathy (CTE). Objective: To explore the relationship between sports career-related concussions and the subsequent occurrence of symptoms of CMD among former male professional athletes. Design: Cross-sectional analyses performed on baseline electronic questionnaires from three prospective cohort studies. Setting: National unions or players' associations in professional football, ice hockey and rugby. Patients (or Participants): A total of 576 former male professional athletes were enrolled. Mean age at recruitment was 37 years; mean duration of sports career was 10 years. Interventions (or Assessment of Risk Factors): The total number of confirmed concussion incidents during an athlete's career and diagnosed by a medical professional was examined. Main Outcome Measurements: Several Patient Reported Outcome Measures (PROMs) were included and assessed with validated scales, namely symptoms of distress, anxiety/depression, sleep disturbance, adverse alcohol use. Results: The number of sports career-related concussions was a predictor for all outcome measures (β=0.072–0.100; P≤0.035). Specifically, former professional athletes who reported a history of four or five concussions were approximately 1.5 times more likely to report symptoms of CMD, rising to a two- to four-fold increase in those reporting a history of six or more sports career-related concussions. Conclusions: These data demonstrate a direct relationship between exposure to sports concussion and subsequent risk of symptoms of CMD in former professional athletes across a range of contact sports. Further work to explore the association between sports concussion and symptoms of CMD is required; in meantime strategies for effective risk reduction and improved management appear indicated.